2009
DOI: 10.1007/978-1-4419-5692-7_23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of JM-1232(-), a New Sedative on Central Respiratory Activity in Newborn Rats

Abstract: JM-1232(-), a newly manufactured isoindole derivative, shows sedative effect at a lower concentration compared with propofol. In the present study, we analyzed the response of the central respiratory activity to JM-1232(-). The brainstem-spinal cord of a newborn rat was isolated and was continuously superfused with oxygenated artificial cerebrospinal fluid (ACSF). Rhythmic inspiratory burst activity was recorded from C4 spinal ventral root using a glass suction electrode. We measured C4 burst rate and amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kuribayashi et al reported that JM-1232(-) at between 10 -4 and 5 x 10 -4 mol/L depressed central respiratory activity, and estimated that the hypnotic dose was less than 10 -5 mol/L [ 6 ]. As in rats, the effective concentration of JM-1232(-) in the rabbit is probably well under 10 -5 mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Kuribayashi et al reported that JM-1232(-) at between 10 -4 and 5 x 10 -4 mol/L depressed central respiratory activity, and estimated that the hypnotic dose was less than 10 -5 mol/L [ 6 ]. As in rats, the effective concentration of JM-1232(-) in the rabbit is probably well under 10 -5 mol/L.…”
Section: Discussionmentioning
confidence: 99%